PENGARUH DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT SIIX ELECTRONIC BATAM - Melda Br Manurung; Wasiman Wasiman (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine and analyze the effect of work discipline and career development on employee performance at PT SIIX Electronic Batam. The population in this study amounted to 105 employees. The sample in this study used a saturated sample technique consisting of 105 respondents at PT SIIX Electronic Batam. This type of research is quantitative research and the data used are primary and secondary data obtained from the distribution of questionnaires and a list of statements whose measurement uses a Likert scale. The data collected were analyzed using validity and reliability tests, the classical assumption test in this study used the normality test, multicollinearity test and heteroscedasticity test, the effect test in this study used multiple regression analysis and analysis of the coefficient of determination (R2), while the hypothesis test in this study This test uses T test and F test with the help of SPSS version 25 program. T test results show that work discipline has a significant effect on employee performance and career development has an effect on employee performance. The results of the F test show that work discipline and career development simultaneously have a significant effect on employee performance at PT SIIX Electronic Batam.